Fluoroscopically Guided Facet Cyst Rupture: Rate of Conversion to Surgery and Risk Factor Analysis. Issue 7 (August 2021) - Bell, Joshua; Bhatia, Manminder; Hadeed, Michael M.; George, Jose; Hill, Andrew; Novicoff, Wendy M.; Nacey, Nicolas C.; Shimer, Adam L.
Abstract : Study Design: Retrospective case series at a single academic medical center. Objective: The aim was to determine if specific clinical, radiologic, and procedural factors are associated with conversion to surgery after fluoroscopically guided cyst rupture. Summary of Background Data: Percutaneous fluoroscopic rupture of facet cysts can often be the definitive treatment; however, it is unknown before the procedure who will ultimately proceed to formal surgical decompression. Differences in clinical, radiographic, and procedural factors of facet cysts may relate to the difference in efficacy of fluoroscopically guided cyst rupture. Methods: A continuous cohort of 45 patients who underwent fluoroscopically guided cyst rupture was evaluated. The primary outcome measured rate of conversion to surgery and of those that underwent surgery, the rate of decompression and fusion compared with fusion alone was noted. Secondary outcomes included analysis of clinical, radiologic, and procedural variables to determine if there were risk factors associated with conversion to surgery. Results: Twenty-nine percent of patients eventually underwent a surgical procedure with an average interval to surgery of 95 days after attempted rupture. Thirty-eight percent of patients that underwent surgery had a decompression and fusion. Failure of percutaneous cyst rupture trended toward significance for a future surgical decompression ( P =0.08). Conclusions: Percutaneous facet cyst rupture is potentially a definitive treatment for this condition; however, it is unknown ahead of time who will proceed to definitive surgical decompression. On the basis of the data in this study, less than one-third of patients who had a fluoroscopically guided facet cyst rupture went on to surgery. There were no clinical, radiographic, or procedural details which could be used to robustly predict failure of percutaneous treatment. At this time, it is recommended to continue to attempt this nonoperative treatment intervention when there is a clinical indication after discussion of the risks and benefits with the patient.